Effect of Multispectral Pulsed Light-Emitting Diodes on the Growth, Photosynthetic and Antioxidant Response of Baby Leaf Lettuce (Lactuca sativa L.) - Miliauskienė, Jurga (Plants (Basel), 2021)
The effect of multicolor pulsed light-emitting diode (LED) irradiation on lettuce “Defender” growth, photosynthetic performance and antioxidant properties was studied. The experiments were designed to compare the continuous and pulsed lighting (0.5, 1 kHz; 50% duty ratio) effects of B450, G520, R660 and FR735 lighting components, maintaining total diurnal integral light quantity (DLI 14.4 mol m(−2) day(−1)) constant during the 16-h photoperiod. The results showed that lettuce grown under pulsed irradiation displayed superior growth performance, including a significant enhancement of fresh (~32%) and dry biomass (~36%) and leaf area (~48%). Lettuce cultivated in both pulsed light treatments was characterized by the higher photosynthetic rate, chlorophyll (a,b) and carotenoid concentration. However, the total phenol and antioxidant properties in lettuce were more dependent on the specific pulsed light frequency. Only treatment with 1 kHz frequency was effective for higher phenol content, 2,20-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radical scavenging activity and Fe(2+) reducing antioxidant power (FRAP). Thus, our results propose the role of pulsed LED light in improving the photosynthetic efficiency and antioxidative properties of lettuce plants cultivated indoors. In the future, pulsed lighting techniques should be included in the development of artificial lighting systems in controlled environment agriculture (CEA) to produce high-quality crops with the possibility to save electricity.